Comparative Efficacy of Newly Registered Fungicides for the Management of Alternaria Leaf Spot of Cauliflower in Nepal - Suraj Singh Gangai; Shishir Sharma (Turkish Journal of Agriculture: Food Science and Technology)
One of the major factor contributing to the decreased yield of cauliflower in Nepal is incorrect fungicide selection and dosages. Alternaria leaf spot (ALS) caused by Alternaria brassicicola, is a devastating disease that significantly reduces the quantity and quality of cauliflower. In vitro evaluation of seven different fungicides was done in a completely randomized design with five replications at different doses i.e., 50 ppm, 100 ppm, 150 ppm, and 200 ppm. All the tested fungicides significantly reduced (P≤0.001) mycelial growth of the pathogen in the poisoned food technique. The greatest reduction in mycelium growth was observed with hexaconazole and azoxystrobin + tebuconazole at the lowest tested concentration (50 ppm). Maximum inhibition of A. brassicicola growth was demonstrated by azoxystrobin + propiconazole at 200 ppm, followed by azoxystrobin + difenoconazole and copper oxychloride. The fungicides that were found effective in inhibiting mycelial growth should be tested under field conditions with multi-location and multi-strains pathogens to ensure that they meet specific requirements related to host and environment interaction. This will help to confirm their efficacy and determine the best application doses.